Surface exposure of O1 serotype lipopolysaccharide in Klebsiella pneumoniae strains expressing different K antigens. - Tomás, J M (1991)
Surface exposure of the O1 serotype lipopolysaccharide in encapsulated Klebsiella pneumoniae strains belonging to different serotypes was examined by using the O1 antigen-specific bacteriophages FC3-1 and FC3-2 in conjunction with immunogold electron microscopy and enzyme immunoassays with specific antisera. Despite the presence of the capsular polysaccharide, the O1 antigen was exposed at the cell surface in strains producing K2, K7, K8, K12, K19, K21, K22, K34, K35, K42, K45, K55, K57, K62, K66, K69, and K70 capsular polysaccharides. However, in strains producing K1, K10, and K16 capsular polysaccharides, the O1 antigen was masked by the K antigen. These results suggest that, since the O1 antigen is surface exposed in many different strains of K. pneumoniae with different capsular serotypes and is also able to immunoprotect, its potential as a useful vaccine component should not be overlooked.